SUBROGATED MOTHERHOOD IN MEXICO - Bejerano Morales, Valeria; Antonio Morales Notario, José (Revista Gênero e Interdisciplinaridade, 2021)
This is an analysis of how surrogacy in motherhood is contemplated in Mexican legislation, it is specified and searched for a concise explanation of the general concepts of motherhood and surrogacy; that with a view to a citizen perspective, given the little disclosure and the scant regulation of the subject within Mexican laws. Likewise, it is mention the details of the state’s legislation that have been in charge of deepening or, at least, regulating certain points of said medical practice. It is important to visualize that, at a certain moment, surrogacy will be practiced more frequently in order to satisfy the needs of women or couples who resort to this method to bring a life with them and thus form a family model in a more effective way. Easy and closer to the naturalness possible, leaving aside the different beliefs of our society regarding surrogacy and the use of technological elements in conception. It is important to take into account the indispensable volitional role of a woman who agrees to lend or rent her womb; since in various case studies, as well as in the antecedents raised (such is the case of Baby M), the surrogate mothers refuse to deliver the baby to the contracting parents, which generates controversy and legal disputes, which in the absence of regulation, they cannot be taken care of in a correct way.